Who owns the future city? Phases of technological urbanism and shifts in sovereignty. (June 2021) - Sadowski, Jathan
Smart urbanism has, over the last decade or so, grown to become a major research area within the social science of cities and digital technology. This critical commentary aims to outline a new framework for analysing the urban political economic dynamics currently unfolding through different combinations of power, technology and capital in cities. Rather than simply spreading via one static model of smart urbanism, the practices and purposes for rolling out digital technology in cities continue to evolve in important ways. I integrate the established research on smart urbanism with emerging work on 'platform urbanism', thus providing a coherent and forward-looking analysis of how various techno-political trends are connected yet distinct. In broad brushstrokes, over the last decade the urbanisation of technology capital has happened in concurrent phases, with each one seeking to take hold over a different aspect of the city: oversight of city governance, operation of city services and ownership of city space. I conclude by linking this political economic analysis to questions about fundamental shifts in urban sovereignty as technology companies move beyond treating the city merely as a place to extract value from and start thinking of it as also a space to exercise dominion over.